Abnormalities of resting-state EEG in patients with prodromal and overt dementia with Lewy bodies: Relation to clinical symptoms. Issue 11 (November 2020) - Pascarelli, Maria Teresa; Del Percio, Claudio; De Pandis, Maria Francesca; Ferri, Raffaele; Lizio, Roberta; Noce, Giuseppe; Lopez, Susanna; Rizzo, Marco; Soricelli, Andrea; Nobili, Flavio; Arnaldi, Dario; Famà, Francesco; et al.
Highlights: Patients with prodromal-overt dementia with Lewy bodies (DLB) and visual hallucinations show highest parietal delta rhythms. DLB patients with the greatest cognitive deficits show highest posterior alpha rhythms. EEG rhythms are related to clinical manifestations in DLB patients. Abstract: Objective: Here we tested if cortical sources of resting state electroencephalographic (rsEEG) rhythms may differ in sub-groups of patients with prodromal and overt dementia with Lewy bodies (DLB) as a function of relevant clinical symptoms. Methods: We extracted clinical, demographic and rsEEG datasets in matched DLB patients (N = 60) and control Alzheimer's disease (AD, N = 60) and healthy elderly (Nold, N = 60) seniors from our international database. The eLORETA freeware was used to estimate cortical rsEEG sources. Results: As compared to the Nold group, the DLB and AD groups generally exhibited greater spatially distributed delta source activities (DLB > AD) and lower alpha source activities posteriorly (AD > DLB). As compared to the DLB "controls", the DLB patients with (1) rapid eye movement (REM) sleep behavior disorders showed lower central alpha source activities (p < 0.005); (2) greater cognitive deficits exhibited higher parietal and central theta source activities as well as higher central, parietal, and occipital alpha source activities (p < 0.01); (3) visual hallucinations pointed to greater parietal delta source activities (p < 0.005). Conclusions: Relevant clinical features were associated with abnormalities in spatial and frequency features of rsEEG source activities in DLB patients. Significance: Those features may be used as neurophysiological surrogate endpoints of clinical symptoms in DLB patients in future cross-validation prospective studies.